Getting physical with the market: a study of metaphors in the business times - Tengku Mahmood, Tengku Farah Petri; Mohd Ali, Afida; Rafik Galea, Shameem; Mohd Kasim, Zalina (Universiti Putra Malaysia Press, 2012)
This study investigates the metaphorical linguistic manifestations of the conceptual metaphor, market movements are physical movements, using Charteris-Black and Ennis’s (2001) notion of conceptual metaphors. Following a corpus linguistic approach for data collection purposes, it analysed 50 unique Business Times articles randomly identified from a total of 292 articles. An expert within the business context provided expertise in the interpretation of specific types of data derived from the corpus. The findings show that the metaphorical linguistic expressions generally concretise the abstract concept of the economy and market movements and mainly comprise of verbs and nouns. This paper illustrates some of the examples of the relevant metaphorical expressions and discusses how the domain of physical movements helps to structure the domain of market movements. The findings of this study, however, can only be generalised to the samples involved in this study.